Nuclear reprogramming of sperm and somatic nuclei in eggs and oocytes. (4th June 2013) - Teperek, Marta; Miyamoto, Kei
Abstract: Eggs and oocytes have a prominent ability to reprogram sperm nuclei for ensuring embryonic development. The reprogramming activity that eggs/oocytes intrinsically have towards sperm is utilised to reprogram somatic nuclei injected into eggs/oocytes in nuclear transfer (NT) embryos. NT embryos of various species can give rise to cloned animals, demonstrating that eggs/oocytes can confer totipotency even to somatic nuclei. However, many studies indicate that reprogramming of somatic nuclei is not as efficient as that of sperm nuclei. In this review, we explain how and why sperm and somatic nuclei are differentially reprogrammed in eggs/oocytes. Recent studies have shown that sperm chromatin is epigenetically modified to be adequate for early embryonic development, while somatic nuclei do not have such modifications. Moreover, epigenetic memories encoded in sperm chromatin are transgenerationally inherited, implying unique roles of sperm. We also discuss whether somatic nuclei can be artificially modified to acquire sperm‐like chromatin states in order to increase the efficiency of nuclear reprogramming.